The Liquidity Effects of Money Shocks on Short Term Interest Rates in the Selected ASEAN Countries - Engku Ariff, Engku Elini (2005)
The main purpose of this study is to empirically investigate the liquidity effects of money shocks on short-term interest rates. The research was done for selected five ASEAN countries, namely Indonesia, Malaysia, the Philippines, Singapore and Thailand. Monthly data was used in the analysis covering the period of 1983:Ol to 2000: 12. Empirical evidences based on the unit root test using Augmented Dicky Fuller (ADF) test showed that all the variables (consumer price index, money market rate or T-bill rate, wholesale price or industrial production or production price, money supply and US T-bill rates) were I (1) which means that all these series under study are non-stationary in the level forms, but stationary in the first difference. Johansen co-integration analyses identified that all the models represented by the five variables were co-integrated within the system of five variables. The vector autoregressive systems estimation method (VAR) was employed for this co integration test. The vector error correction model (VECM) was used to capture the influence of the variables in long-run relationships. The VECM approach distinguished between the 'short-term; and 'long-term' Granger causality. Impulse response functions (IRFs) were then applied to test the significance effects of the short-term domestic interest rate variable due to a shock of one standard deviations innovation. The empirical evidences obtained from this study suggested that the Johansen-Juselius multivariate co-integration indicated the existence of a stable long-run relationship between the five variables. On the other hand, the results also showed that all models in five variables were co-integrated within the equation system. The Granger causal relationship however showed a different causality for each of the countries. The Singapore and the Philippines results indicated that money supply did not affect other variables in both the short-run and long-run. However, in Thailand, consumer price index did not show effects in the short-run but was statistically significant in the longrun. For the remaining countries, all the variables also affected each other in the shortrun, but opposite results were obtained for the long-run relationships. The estimation of error correction term that identified the adjustment showed that Thailand is the fastest country to adjust to the system estimation. The inflation expectation effect was not representative for all the selected countries. The income effects thus, occurred in only two out of five countries. Impulse response function (IRFs) test was employed to investigate the existence of liquidity effects of money shocks on short-term interest rates. Liquidity effects do exists in Asean countries but were of different patterns and for different duration. A negative effect of domestic short-tenn interest rate immediately occurred after the money shocks for all countries accept Indonesia. The longest effect was found for Malaysia while the shortest was on the Philippines, which was only for five months. This was followed by Singapore (less than ten months). Thailand initially showed negative response for a brief period, turning positive, and ultimately negative. However, Indonesia showed the existence of liquidity effect only after twenty months subsequent to the money shock. Empirical evidences and findings from this study conclusively found that liquidity effects do exists in the ASEAN countries which each country registering its own pattern and length. This is acceptable considering the large variations in the economy variables and the financial institutional foundation between the five countries studied.